Identification of HuR target circular RNAs uncovers suppression of PABPN1 translation by CircPABPN1. Issue 3 (4th March 2017) - Abdelmohsen, Kotb; Panda, Amaresh C.; Munk, Rachel; Grammatikakis, Ioannis; Dudekula, Dawood B.; De, Supriyo; Kim, Jiyoung; Noh, Ji Heon; Kim, Kyoung Mi; Martindale, Jennifer L.; Gorospe, Myriam
ABSTRACT: HuR influences gene expression programs and hence cellular phenotypes by binding to hundreds of coding and noncoding linear RNAs. However, whether HuR binds to circular RNAs (circRNAs) and impacts on their function is unknown. Here, we have identified en masse circRNAs binding HuR in human cervical carcinoma HeLa cells. One of the most prominent HuR target circRNAs was hsa_circ_0031288, renamed CircPABPN1 as it arises from the PABPN1 pre-mRNA. Further analysis revealed that HuR did not influence CircPABPN1 abundance; interestingly, however, high levels of CircPABPN1 suppressed HuR binding to PABPN1 mRNA. Evaluation of PABPN1 mRNA polysomes indicated that PABPN1 translation was modulated positively by HuR and hence negatively by CircPABPN1 . We propose that the extensive binding of CircPABPN1 to HuR prevents HuR binding to PABPN1 mRNA and lowers PABPN1 translation, providing the first example of competition between a circRNA and its cognate mRNA for an RBP that affects translation.